2008
DOI: 10.1002/ptr.2455
|View full text |Cite
|
Sign up to set email alerts
|

Food supplementation with an olive (Olea europaea L.) leaf extract reduces blood pressure in borderline hypertensive monozygotic twins

Abstract: Hypertension is a harmful disease factor that develops unnoticed over time. The treatment of hypertension is aimed at an early diagnosis followed by adequate lifestyle changes rather than pharmacological treatment. The olive leaf extract EFLA943, having antihypertensive actions in rats, was tested as a food supplement in an open study including 40 borderline hypertensive monozygotic twins. Twins of each pair were assigned to different groups receiving 500 or 1000 mg/day EFLA943 for 8 weeks, or advice on a favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 17 publications
4
105
1
2
Order By: Relevance
“…However, human studies are needed to clearly establish olive leaf as a potential treatment for high blood pressure [42]. With this respect, a prophylactic blood pressure lowers and cholesterol lowers actions of the olive leaf extract EFLA ® 943 in human was studied by Perrinjaquet-Moccetti et al [38]. The study confirmed the antihypertensive and cholesterol lowering actions of the extract in human [38].…”
Section: Olive Leaf Extract and High Blood Pressurementioning
confidence: 96%
See 4 more Smart Citations
“…However, human studies are needed to clearly establish olive leaf as a potential treatment for high blood pressure [42]. With this respect, a prophylactic blood pressure lowers and cholesterol lowers actions of the olive leaf extract EFLA ® 943 in human was studied by Perrinjaquet-Moccetti et al [38]. The study confirmed the antihypertensive and cholesterol lowering actions of the extract in human [38].…”
Section: Olive Leaf Extract and High Blood Pressurementioning
confidence: 96%
“…By increasing nitric oxide production, oleuropein appears to arm the macrophages against endotoxins (bacterial poisons generated by gram-negative bacteria). Interestingly, oleuropein only increased nitric oxide production when endotoxins were present [5,38].…”
Section: Antibacterial Effectmentioning
confidence: 96%
See 3 more Smart Citations